HUBUNGAN DUKUNGAN SOSIAL DENGAN DEPRESI PADA PASIEN PASCA STROKE (Studi Analitik Observasional di Rumah Sakit Islam Sultan Agung Semarang) - Rosdiana, Ika (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
Stroke is one of diseases which can be the number one cause of disability in the worldx and cause of death number two in the world. The incidence of stroke increases with increasing age. The purpose of this study was to determine the relationship of social support with depression in stroke patients. This type of research uses analytic observation with cross sectional design. The sample used was non-hemorrhagic post-stroke patients and post-stroke hemorrhagic outpatients in the medical rehabilitation clinic of Sultan Agung Islamic Hospital Semarang by taking into account the inclusion and exclusion criteria. Data collection by visiting the patient's house and conducting interviews using social support questionnaires and BDI. Data analysis using Pearson test. The results obtained were 84 non-hemorrhagic stroke patients and 30 hemorrhagic stroke patients. Most age is experienced at the age of 61-70 years as much as 45.2% in non-hemorrhagic strokes and 43% in hemorrhagic strokes. The most sex is female 53.6% in non-hemorrhagic stroke and 60% in men in hemorrhagic stroke. In non-hemorrhagic stroke patients, it was found that 92.9% received high social support while in hemorrhagic stroke patients, high social support was 73,3%. The degree of depression obtained a minimum of 85.7% depression according to the BDI scale for non-hemorrhagic stroke patients and the severe BDI scale of 43.3% for hemorrhagic stroke patients. There was no significant relationship between social support and the degree of depression in non-hemorrhagic stroke patients hemorrhagic stroke patient The conclusion was not found a meaningful relationship between social support and depression level in non-hemorrhagic and hemorrhagic post-stroke patients